Short-Term Total Sleep-Deprivation Impairs Contextual Fear Memory, and Contextual Fear-Conditioning Reduces REM Sleep in Moderately Anxious Swiss Mice - Qureshi, Munazah F.; Jha, Sushil K. (Frontiers in Behavioral Neuroscience, 2017)
The conditioning tasks have been widely used to model fear and anxiety and to study their association with sleep. Many reports suggest that sleep plays a vital role in the consolidation of fear memory. Studies have also demonstrated that fear-conditioning influences sleep differently in mice strains having a low or high anxiety level. It is, therefore, necessary to know, how sleep influences fear-conditioning and how fear-conditioning induces changes in sleep architecture in moderate anxious strains. We have used Swiss mice, a moderate anxious strain, to study the effects of (i) sleep deprivation on contextual fear conditioned memory, and also (ii) contextual fear conditioning on sleep architecture. Animals were divided into three groups: (a) non-sleep deprived (NSD) (b) stress control (SC) and (c) sleep-deprived (SD) groups. The SD animals were sleep deprived for 5h soon after training. We found that the NSD and SC animals showed 60.57% and 58.12% freezing on the testing day, while SD animals showed significantly less freezing (17.13% only) (p<0.001) on the testing day. Further, we observed that contextual fear-conditioning did not alter the total amount of wakefulness and NREM sleep. REM sleep, however, significantly decreased in NSD and SC animals on the training and testing days. Interestingly, REM sleep did not decrease in the SD animals on the testing day. Our results suggest that short-term sleep deprivation impairs fear memory in moderate anxious mice. It also suggests that NREM sleep, but not REM sleep, may have an obligatory role in memory consolidation.